An Assessment of the Validity of an Audio-Video Method of Food Journaling for Dietary Quantity and Quality - Emily Jago; Alain P. Gauthier; Ann Pegoraro; Sandra C. Dorman (Journal of Nutrition and Metabolism)
Objective. To validate an audio-video (AV) method of food journaling, in a free-living scenario, compared to direct, weighed food assessment. Design and Setting. Data were collected in a cafeteria. Meals, selected by participants (n=30), were documented using the AV method: participants video-recorded their tray while audio-recording a description of their selected meal, after which the research team digitally weighed each food item and created an itemized diary record of the food. Variables Measured. Data from the AV method and from the weighed food diaries were transcribed and entered into a nutrition software analysis program (Nutribase Pro 10.0). Nutrient outputs were compared between the two methods including kilocalories, macronutrients, and selected micronutrients. Analyses. Using mean scores for each variable, Wilcoxon signed-rank test and Spearman’s correlation coefficients were conducted. Interclass correlation coefficient (ICC) was calculated for absolute agreement between the two methods to assess interrater reliability. Results. With the exception of Vitamin E and total weight, nutrient values were highly correlated between methods and were statistically significant given alpha = 0.05, power = 0.95, and effect size of 0.70. Conclusions. The AV method may be a meaningful alternative to diary recording in a free-living setting.